1997
DOI: 10.1212/wnl.48.3.602
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric migraine and the International Headache Society (IHS) criteria

Abstract: The IHS criteria for migraine without aura have poor sensitivity but high specificity using a clinical diagnosis as the gold standard. The IHS criteria should be modified to better reflect current pediatric clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
188
0
16

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(214 citation statements)
references
References 8 publications
10
188
0
16
Order By: Relevance
“…Since 1992, many papers have shown the high specificity but low sensitivity of ICHD-I diagnostic criteria for migraine without aura in childhood [3][4][5][6][7][8][9][10][11][12][13][14][15]. Several published series have shown that the percentage of children in which the attack duration is less than 2 hours ranged from 11% to 32% [3,5,7,8,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 1992, many papers have shown the high specificity but low sensitivity of ICHD-I diagnostic criteria for migraine without aura in childhood [3][4][5][6][7][8][9][10][11][12][13][14][15]. Several published series have shown that the percentage of children in which the attack duration is less than 2 hours ranged from 11% to 32% [3,5,7,8,11].…”
Section: Discussionmentioning
confidence: 99%
“…Several published series have shown that the percentage of children in which the attack duration is less than 2 hours ranged from 11% to 32% [3,5,7,8,11]. This fact has the been seen as main reason for the low sensitivity of the aforementioned criteria.…”
Section: Discussionmentioning
confidence: 99%
“…meters have been discussed both for migraine and tensiontype headache [7][8][9][10][11][12][13][14][15]. The suggested changes to IHS criteria for the diagnosis of migraine in children refer to shorter duration, not always unilateral localization, and the variable occurrence of photophobia and phonophobia.…”
Section: S98mentioning
confidence: 99%
“…2,3 Children rarely present with auras, but often exhibit autonomic symptoms such as pallor, nausea, vomiting and abdominal pain.…”
mentioning
confidence: 99%